Peningkatan Efisiensi pada Instansi Perguruan Tinggi Menggunakan Sistem Informasi Akademik - Agung Wijoyo; Fuad Mustamirrul Ishlah; Iqbalsyah Khatami; Muhammad Fadhly Noor Rizqi; Yordan Marcelino Marcus; Muhammad Afif Alrasyid; Syukri Halim (Journal of Research and Publication Innovation, 2023)
This journal discusses the use of Academic Information Systems (AIS) in academic environments to manage various activities, ranging from student data management, class schedules, financial management, to academic performance processing. The article provides a definition and explanation of the main components of AIS and the features that can be integrated into the system. In addition, this journal also discusses the challenges and obstacles that arise in the use of AIS, including cost issues, human resources, technological infrastructure limitations, and system incompatibility issues. In conclusion, the authors review the convenience and benefits that can be obtained from the use of academic information systems.